Translation Errors in English-Indonesian President’s Speech Text Produced by Students of the Sixth Semester of English Education Program at STKIP Kie Raha Ternate - Ririn Yastiawijaya (Jurnal Langua, 2018)
English students are always taught four language skills; listening, speaking, reading and writing. Besides the skills mentioned above, there is still one of the very important aspects encouraging the foreign language in teaching and learning process, namely translation. Thus, having ability in translation becomes a primary necessity for students who learn language especially foreign language. In Indonesia for example, English taught as a foreign language. However, there are often cases where translation contains errors and if there are errors in translation, the real message of the text is not communicated well. There could be misunderstanding because of error in translation. Based on the phenomenon, the researcher was interest to the research of the translation error. The researcher focused the research in the sixth semester student of English Education Program at STKIP Kie Raha Ternate consist of 31 students, because they have gotten the lectures of Translation, so at least they have already a bit knowledge. The data were taken from 18 students only as samples. The researcher collected the data by gave the students an English text to be translated into Indonesian. The research used descriptive qualitative method because the research attempted to find their errors in translating text. It means that the research aimed to find what kinds of error they might make. In analyzed the data, the researcher identified and classified the errors based on their types. The analysis of the data showed the student errors in translating English text. Based on the data analysis, the researcher found that the students committed errors in Omission (1700 or 97.3%), Misinformation (31 or 1.8%), and Addition (16 or 0.9%).